Short-term effect of particulate air pollutant on the risk of tuberculosis outpatient visits: A multicity ecological study in Anhui, China. (1st July 2022) - Wang, Xin-Qiang; Huang, Kai; Cheng, Xin; Hu, Cheng-Yang; Ding, Kun; Yang, Xiao-Jing; Zhang, Kang-Di; Yu, Wen-Jie; Wang, Jie; Li, Ying-Qing; Chen, Shuang-Shuang; Zhang, Xiu-Jun; et al.
Abstract: Tuberculosis (TB) causes about 10 million new cases and 1.5 million deaths every year, as the World Health Organization's Global Tuberculosis Report shows. We aimed to investigate the association between short-term exposure to particulate pollutants and the risk of tuberculosis outpatient visits in 16 cities of Anhui Province, China, during the period 2015–2020, and to provide more evidence for the relationship between tuberculosis and air pollution. In this study, we analyzed the data using a variety of models, including Poisson's generalized linear regression model, distributed lag non-linear model (DLNM) and random effects model. We assessed the relationship between particulate matter exposure and tuberculosis using a 28-day cumulative lag effect for every 10 unit increases in pollutant concentration and 95% CI. We performed stratified analyses for gender and age. Age stratification included <18 years old group, 19–64 years old group and >64 years old group and gender stratification included male group and female group, and then we performed a sensitivity analysis to test the stability of the results. The overall effect values of PM2.5 and PM10 were RR = 1.031 (95%CI: 1.019–1.043) and RR = 1.023 (95%CI: 1.016–1.030), respectively. Estimation for individual cities showed that the strongest association between PM2.5 and the risk of TB outpatient visits was observed in Tongling, with an RR of 1.136 (95%CI: 1.0261–1.2583), also the PM10 in Suzhou, with an RR of 1.0629 (95%CI: 1.0421–1.0842). Stratified analysis showed that particulate matter exposure had a more significant impact on males and the elderly, and that there was little association between particulate matter exposure and TB risk in children and adolescents. Exposure to PM2.5 and PM10 increases the risk of TB outpatient visits. Males and the elderly are vulnerable groups, and different prevention and control strategies should be developed for different groups to reduce the burden of TB. Highlights: China's first province-wide study on the TB outpatient visits and particulate pollutants. Exposure to particulate pollutants increases the risk of tuberculosis outpatient visits. Exposure to particulate pollutants has a greater impact on male and the elderly.